Amount, Source, and Quality of Support as Predictors of Women's Birth Evaluations. Issue 3 (17th March 2016) - Simon, Richard M.; Johnson, Katherine M.; Liddell, Jessica
Abstract: Background: This paper examines the separate effects of the perceived amount, source, and quality of support during labor and delivery on women's positive and negative evaluations of their birth experiences. Methods: Data come from the Listening to Mothers I and II (LTM) surveys ( n = 2, 765). Women's perception of support was regressed separately onto indices of positive and negative words that women associated with their labor and delivery. Results: The total number of support sources, type of support person, and quality of support all impacted women's birth evaluations across different regression models, controlling for demographics, birth interventions, and other birth characteristics. Support overall had a greater effect on increasing women's positive evaluations, but was not as protective against negative evaluations. Support from medical and birth professionals (doctors, nurses, doulas) had the greatest effect on women's positive evaluations. Good partner support was complexly related: it was associated with less positive evaluations but also appeared to have a protective effect against negative birth evaluations. Discussion: Support in childbirth is a complex concept with multiple dimensions that matter for women's birth evaluations. Support from nursing staff, doctors, and doulas is important for enabling positive evaluations while support from partners is more complexly related to women's evaluations. Research on support for laboring women should more extensively address the division of labor between different sources of support.